SARS-CoV-2-Triggered Hemophagocytic Lymphohistiocytosis with Complications of Posterior Reversible Encephalopathy Syndrome - Ross M. Perry; Scott D. Casey; Alex Q. Lee; Sylvia P. Bowditch; Mary A. Rasmussen; Viyeka Sethi; Arun R. Panigrahi (Case Reports in Pediatrics)
In this article, we describe a novel case of SARS-CoV-2-associated-hemophagocytic lymphohistiocytosis (HLH) complicated by posterior reversible encephalopathy syndrome (PRES). Initially diagnosed with multisystem inflammatory response in children (MIS-C), the patient received a large corticosteroid dose days before the onset of neurological symptoms. After developing PRES, the patient was treated with antihypertensives, antiepileptics, dexamethasone, and anakinra, leading to neurologic normalization. We propose that given the challenging diagnostic picture of PRES developing in patients with HLH or MIS-C, institutionalized standards for blood pressure management during corticosteroid induction may significantly improve outcomes in patients being treated for hyperinflammatory syndromes who develop neurological symptoms.